Impact of the Pandemic on the Socio-Economic Development of Кazakhstan - Kh. N. Sansyzbayeva; L. Zh. Ashirbekova; T. Pisula; A. A. Musulmankulova (Экономика: стратегия и практика, 2022)
COVID-19 has affected all aspects of public life, sectors of the national economy, and the standard of living of the population in both positive and negative directions. The government of Kazakhstan played a significant role in reducing the negative consequences of the pandemic on the socio-economic situation of the population by implementing state support measures. However, systemic social problems, both globally and nationally, have not been resolved. The World Health Organization was not ready for the global coronavirus crisis. The search in the global world for ways to combat new modifications of the viral epidemic remains relevant. The global community must be prepared for unexpected viral diseases. The purpose of the study is to conduct a qualitative analysis of the main changes in the socio-economicsphere of Kazakhstan associated with the spread of coronavirus in the world in order to determine the necessary socio-economic and institutional processes and impacts that can have a significant impact on society in the long term. The article highlights social problems, the solution of which will contribute to the development of human capital and the economic growth of the country. Complex methods of systemic and empirical analysis were used in this article. Analysis of socio-economic development confirmed the proposed hypotheses. As a result of the study, the features of the socio-economic development in the current situation are determined. An attempt has been made to identify the main trends, and processes necessary for fundamental changes in the socio-economic life of the country in the post-pandemic period.